Multi‐omics profiling of CHO parental hosts reveals cell line‐specific variations in bioprocessing traits. Issue 9 (20th May 2019) - Lakshmanan, Meiyappan; Kok, Yee Jiun; Lee, Alison P.; Kyriakopoulos, Sarantos; Lim, Hsueh Lee; Teo, Gavin; Poh, Swan Li; Tang, Wen Qin; Hong, Jongkwang; Tan, Andy Hee‐Meng; Bi, Xuezhi; Ho, Ying Swan; et al.
Abstract: Chinese hamster ovary (CHO) cells are the most prevalent mammalian cell factories for producing recombinant therapeutic proteins due to their ability to synthesize human‐like post‐translational modifications and ease of maintenance in suspension cultures. Currently, a wide variety of CHO host cell lines has been developed; substantial differences exist in their phenotypes even when transfected with the same target vector. However, relatively less is known about the influence of their inherited genetic heterogeneity on phenotypic traits and production potential from the bioprocessing point of view. Herein, we present a global transcriptome and proteome profiling of three commonly used parental cell lines (CHO‐K1, CHO‐DXB11, and CHO‐DG44) in suspension cultures and further report their growth‐related characteristics, and N ‐ and O ‐glycosylation patterns of host cell proteins (HCPs). The comparative multi‐omics and subsequent genome‐scale metabolic network model‐based enrichment analyses indicated that some physiological variations of CHO cells grown in the same media are possibly originated from the genetic deficits, particularly in the cell‐cycle progression. Moreover, the dihydrofolate reductase deficient DG44 and DXB11 possess relatively less active metabolism when compared to K1 cells. The protein processing abilities and the N ‐ and O ‐glycosylation profiles also differ significantly across the host cell lines, suggesting the need to select host cells in a rational manner for the cell line development on the basis of recombinant protein being produced. Abstract : A mammalian systems biotechnology approach exploited multi‐omics profiles together with genome‐scale metabolic network model to systematically link the possible phenotypic differences across Chinese hamster ovary (CHO) host cell lines with their genotypes. The current work highlights that the genetic diversity and heterogeneity of CHO cells indeed affect their growth phenotype as well as glycosylation patterns, thus serving as a good starting point for the rational selection of relevant CHO host cells as well as to establish cell line engineering targets.